A new History Education lecturer’s university experiences during Covid-19: A personal reflection (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
On March 16th, 2020 I commenced my new job as a lecturer on History Education at Stellenbosch University (US), the very same day the University went into lockdown due to COVID-19. I have been a high school teacher for 11 years and so, moving to the University sectors brought with its own challenges. Added to these obstacles was now the addition of remote learning and the complete upheaval of University life. I have attempted to unpack my own experiences as a junior staff member during a nationwide pandemic lockdown and my experiences with remote teaching and learning. This is a personal reflection which outlines my experiences, as well as lessons I have taken away from the transition to online teaching. There are many obstacles that new lecturers face however, these challenges have been exacerbated due to the sudden transition to remote teaching and learning.
Keywords: Remote teaching; Remote learning; Online; New lecturer; COVID-19; Pandemic; History Education lecturer